BLUE ECONOMY DEVELOPMENT IN INDONESIA - Oksana Razladova; Antonio E. L. Nyoko (Universitas Nusa Cendana, 2022)
This work is highlighting the possibilities to enhance blue economy development in Indonesia with environmentally friendly and sustainable solutions to assure successful future and growth. Literatures review and Focus Group Discussion were conducted to collect Indonesia profiles and potential factors to be developed in blue economic strategic planning. Blue economy employment opportunities would enhance gender balance also due to specialization job offers where females proved to be potentially more productive than males. Marine Spatial Planning (MSP) originates from nature conservation approach in the Great Barrier Reef. MSP has gain since then a lot of attention due to overused of marine areas. Ecosystem based approach for MSP could result in clean, healthy, safe, productive, and diverse ocean. It could influence where and when the human activities could occur. MSP normally require authority to plan the one and another to implement. Funding normally has government based but could be supported with grants, partnerships, and private sector funding. All activities have to be monitored to assure progress of achievements and environmental effect. Keywords: Blue Economy Development, Indonesia, Gresik, Marine Spatial Planning